Internationalization of Higher Education and Research in Ethiopia: Considerations for Institutional Strategy - Woldegiyorgis, Ayenachew Assefa (Bahir Dar Journal of Education, 2018)
In Ethiopia, research is not only small in size but also largely set as acomponent of the higher education system. Therefore, policy and strategicdecisions at national level are often developed in blended manner thatencompasses both aspects. Internationalization has for the first time emerged as apolicy issue in the fifth Education Sector Development Program, in whichresearch also gained attention, though less than deserved. This paper examinesthe practice of internationalization of higher education at institutional level andthe existing loose-defined policy space. Finally, the paper outlines possibleinstitutional strategies for the internationalization of research.